Cyclic olefin copolymer‐based copper clad laminate and the application for low loss broadband baluns. Issue 2 (29th October 2021) - Zheng, Shimin; Chen, Haidong; Chen, Huibing; Zhang, Wenhai; Xue, Quan; Che, Wenquan
Abstract: In this article, a novel copper clad laminate based on cyclic olefin copolymer (COC) is proposed and manufactured by using lamination process. The loss characteristic of manufactured laminate is investigated by comparing the measured results of two microstrips on proposed COC‐based laminate and traditional Rogers RT/duroid 5880, respectively. Moreover, the SIW/HMSIW baluns operated at X‐band are designed on the proposed laminate, and the measured results verify the inherent out‐of‐phase performance and good amplitude characteristics in broadband frequency range. This work shows a novel type of high‐frequency circuit boards on COC material, which is significantly to be one of the advanced candidates for microwave/millimeter wave circuit applications.